Proteomic approach for understanding milder neurotoxicity of Carfilzomib against Bortezomib - YILMAZ, BETÜL (NATURE PUBLISHING GROUP, 2018)
The proteasomal system is responsible for the turnover of damaged proteins. Because of its important functions in oncogenesis, inhibiting the proteasomal system is a promising therapeutic approach for cancer treatment. Bortezomib (BTZ) is the first proteasome inhibitor approved by FDA for clinical applications. However neuropathic side effects are dose limiting for BTZ as many other chemotherapeutic agents. Therefore second-generation proteasome inhibitors have been developed including carfilzomib (CFZ). Aim of the present work was investigating the mechanisms of peripheral neuropathy triggered by the proteasome inhibitor BTZ and comparing the pathways affected by BTZ and CFZ, respectively. Neural stem cells, isolated from the cortex of E14 mouse embryos, were treated with BTZ and CFZ and mass spectrometry was used to compare the global protein pool of treated cells. BTZ was shown to cause more severe cytoskeletal damage, which is crucial in neural cell integrity. Excessive protein carbonylation and actin filament destabilization were also detected following BTZ treatment that was lower following CFZ treatment. Our data on cytoskeletal proteins, chaperone system, and protein oxidation may explain the milder neurotoxic effects of CFZ in clinical applications.
Keywords: PROTEASOME INHIBITOR BORTEZOMIB; PROTEIN DISULFIDE-ISOMERASE; MANTLE CELL LYMPHOMA; PERIPHERAL NEUROPATHY; MULTIPLE-MYELOMA; INTERMEDIATE-FILAMENTS; ENDOPLASMIC-RETICULUM; CANCER-THERAPY; STEM-CELLS; HEAT-SHOCK